2021
DOI: 10.9734/afsj/2021/v20i530294
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Pan Bread from Chia Seeds Powder as Substitute Wheat Flour

Abstract: As part of this functional food covenant, the world is searching for new healthy food products with ample quantities of bioactive components such as fibre, mineral elements, essential amino acids, and phenols. Since CHIA seeds powder has both nutritious and pharmaceutical  properties, integrating it into pan bread  may be  beneficial  to  human  health. The sensorial parameters of pan bread enriched with CSP, amino acids composition, and proximate  compositions  of the pan bread were investigated in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…This indicates that DCSF could be an alternative source of dietary fiber and crude protein in toast bread processing. This study was near to the results obtained by Boriy et al (2021) who cleared that pan bread prepared from chia seeds powder increased in protein, ash, crude fiber, and ether extract compared to control pan bread made from wheat flour. 900.20, 25.50, 750, 450, 7.50, 2.50, and 13.50 mց/100ց for Ca, P, Na, K, Mg, Zn, Mn, and Fe, respectively.…”
Section: Chemical Composition and Mineral Contents Of Dcsf And Blends...supporting
confidence: 78%
“…This indicates that DCSF could be an alternative source of dietary fiber and crude protein in toast bread processing. This study was near to the results obtained by Boriy et al (2021) who cleared that pan bread prepared from chia seeds powder increased in protein, ash, crude fiber, and ether extract compared to control pan bread made from wheat flour. 900.20, 25.50, 750, 450, 7.50, 2.50, and 13.50 mց/100ց for Ca, P, Na, K, Mg, Zn, Mn, and Fe, respectively.…”
Section: Chemical Composition and Mineral Contents Of Dcsf And Blends...supporting
confidence: 78%
“…Their study reported that the fortification of organic herbal plant powders significantly increased the mineral contents of wheat bread. Similar research was conducted by Boriy et al 19 when herbal extracts fortified pan bread were developed, and the results of this finding were quite supportive of our work, as the chia seeds fortified bread had high values of minerals like magnesium, iron, zinc, and potassium.…”
Section: Discussionsupporting
confidence: 92%
“…18 As part of this functional food covenant, global communities are looking for fresh, nutritious food items that are rich in bioactive ingredients like fiber, minerals, vital amino acids, and phenols. 19 Worldwide consumption of bakery products like biscuits and cookies is high; however, such foods lack adequate nutritional value. To enhance bakery products with phytochemicals like phenolics, flavonoids, vitamins, minerals, carotenoids, natural colorants, and fiber, the substances from powdered plants, herbs, fruits as well as vegetables may be used as functional ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…The current study's findings are supported by the sensory analysis of a study by Bolarinwa et al [69], which found that the bread made with 5% moringa was not significantly different from the bread made with 100% wheat flour in terms of the majority of the quality attributes assessed in their study. Similar findings were also present in the research work by Boriy et al [70] during the development of pan breads. Another study by Omima et al [55] reported 10% strawberry powder as the optimum level of replacement for wheat flour biscuits.…”
Section: Sensory Evaluation Of Orange Seed Powder-incorporatedsupporting
confidence: 91%